2019
DOI: 10.1101/2019.12.19.881979
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell cycle dynamics of lamina associated DNA

Abstract: words)In mammalian interphase nuclei more than one thousand large genomic regions are positioned at the nuclear lamina (NL). These lamina associated domains (LADs) are involved in gene regulation and may provide a backbone for the overall folding of interphase chromosomes. While LADs have been characterized in great detail, little is known about their dynamics during interphase, in particular at the onset of G1 phase and during DNA replication. To study these dynamics, we developed an antibody-based variant of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(37 citation statements)
references
References 69 publications
(97 reference statements)
1
35
1
Order By: Relevance
“…We found that during early G1 the chromatin associated with the reforming NL are the sub-telomeric regions. This observation was also observed using the novel protein A-DamID approach described by van Steensel and colleagues (26). Interestingly, one sub-compartment, HCT116 C10_7, predicted by CscoreTool-M is very similar to the early G1 LADs mapped by our cTSA-seq.…”
Section: Inferring G1 Genome Organization In a Population Of Asynchro...supporting
confidence: 85%
“…We found that during early G1 the chromatin associated with the reforming NL are the sub-telomeric regions. This observation was also observed using the novel protein A-DamID approach described by van Steensel and colleagues (26). Interestingly, one sub-compartment, HCT116 C10_7, predicted by CscoreTool-M is very similar to the early G1 LADs mapped by our cTSA-seq.…”
Section: Inferring G1 Genome Organization In a Population Of Asynchro...supporting
confidence: 85%
“…We hypothesized that these transitions would be accompanied by a shift in genomic interactions. To test this, we synchronized RPE cells in metaphase and harvested cells at several time points during the cell cycle (van Schaik et al, 2020) to profile Ki-67 interactions. Remarkably, chromosome X does not follow these trends.…”
Section: Cell Cycle Dynamics Of Ki-67 Interactionsmentioning
confidence: 99%
“…We note that, for stem cells and cancer cells, which both have larger volumes, LADs, in fact, are less localized towards the periphery. 102,103 Though a disruption in lamin expression may cause the displacement of LADs from the nuclear envelope, 65,[104][105][106][107] the non-equilibrium mechanisms could contribute to the changes in LADs localization as well.…”
Section: Conclusion and Discussionmentioning
confidence: 99%